"Verily, the White Man's Ways Were the Best": Duncan Campbell Scott, Native Culture, and Assimilation - Salem-Wiseman, Lisa (Studies in Canadian Literature)

(untitled) (None, 1996)
In both Duncan Campbell Scott's administration and his poetry, he showed that Native culture was obsolete, and the Native peoples' only hope for survival was to relinquish their culture and merge with dominant Canadian society. Characteristically, Scott portrays title characters as individuals caught in a transitional stage between Native and white cultures and unable to attain peace in either world.